Paleogene Deposits Distribution of the Kampar Block, Central Sumatra Basin - Abdurrokhim; Budi Muljana; Fikri Muhammad Fiqih (Jurnal Geologi dan Sumberdaya Mineral, 2024)
As the most prolific basin, Central Sumatra Basin is a very mature basin for hydrocarbon exploration. Most of the productive reservoir came from Neogen deposits therefore the stratigraphic reconstruction for depositional environment distribution focused on this deposits. Meanwhile the Paleogene deposits distribution and gross depositional environment (GDE) has not been explore further especially on the southern part on the basin. Paleogen deposits like Kelesa Formation is a syn rift deposition which was deposited in the center of the basin. The lithofacies development of the Kelesa Formation consist of 3 major lithofacies associations: (1) thick-bedded mudstone, (2) Interbedded sandstone and conglomerate, (3) Interbedded sandstones and mudstones. The thick-bedded mudstone is deposited in deep lake setting; interbedded sandstone and conglomerate is interpreted as alluvial fan deposit and interbedded sandstones and mudstones as a fluvial channel. GDE map of Kelesa Formation indicate that sandstones facies developed in fluvial and alluvial fan setting near the basin boundary consider as a potential for future hydrocarbon exploration. Keywords: Kelesa Formation; lithofacies; gross depositional environment; Paleogene deposits